Geochemical characterisation of crude oils from offshore of Sarawak and Sabah - Zainah, Binti Adam (University Malaysia Sarawak, UNIMAS, 2013)
A total of six crude oil samples from Baram and Bokor oilfields at Baram offshore of Miri, Bayan and D35 oilfields at Balingian offshore of Bintulu, Samarang oilfield at offshore of Labuan and South Furious oilfield at offshore of Sabah were studied for their organic geochemical characteristics. The crude oils were fractionated on silica gel column chromatography into aliphatic hydrocarbons, aromatic hydrocarbons and polar compounds. The fractions were analysed by gas chromatography-flame ionization detector (GC-FID) and gas chromatography-mass spectrometer (GC-MS). Ratio of biomarkers such as pristane/phytane, pristane/C17, phytane/C18, carbon preference index (CPI), ΣC21-C31/ΣC15- C20, oleanane/C30hopane, %C27/(C27-C29)steranes, %C28/(C27-C29)steranes, %C29/(C20- C29)steranes and (20S/(C20S+C20R)steranes were used as source correlation indices of crude oil. The presence of 18α (H)-oleanane is an evidence that all crude oils sourced from terrigenous higher plants. Gammacerane detected at trace amount in the Baram, Bokor, Samarang and South Furious crude oils indicating input of marine organic matter under saline environments. The D35 and Bayan crude oils were deposited under oxic conditions of peat swamp environment with high terrestrial organic input. Baram and Bokor crude oils are related to fluviomarine environment, while Samarang crude oil is related to coastal swamp environment. South Furious crude oil was deposited under aquatic depositional environments. Derivatised F3 and F4 fractions have been successfully silylated with tert-butyldimethylsilyl (TBDMS) as shown by the appearance of several additional peaks in the chromatogram of derivatised samples compared to underivatised samples. The varied organic composition of the F3 and F4 fractions showed the crude oils consist of different organic compositions from each other. The fatty acid, ester, aldehyde and ketone groups showed dominance in South Furious crude oil, while nitrogen containing compound and alcohol groups are dominant in Samarang crude oil compared to other crude oils. The FTIR results showed functional groups peaks such as aromatic C-H out of plane and sulfoxide (C2S=O). The similar absorption bands for all spectra of all the crude oils indicated similarity in terms of group compositions. The scanning electron microscope (SEM) analysis for asphaltene in all crude oils showed different structural morphology for crude oils studied. The inductive coupled plasma-optical emission spectrometry (ICP-OES) analysis on crude oils revealed the highest concentration of Fe and Zn in Baram crude oil followed by the Bokor, D35, Samarang, Bayan and South Furious crude oils. Highest concentration of Ni and Ba was recorded in the D35 crude oil, while the highest concentration of Cr was detected in South Furious crude oil. The cluster analysis formed three groups, that are group 1 consists of Samarang and South Furious crude oils, group 2 consists of Baram and Bokor crude oils and group 3 consists of D35 and Bayan crude oils. Furthermore, principal component analysis (PCA) suggests that Baram, Bokor and Bayan crude oils are closely related, whereas D35, Samarang and South Furious crude oils are closely related to each other.